Rhenium (I) Complexes Based on Iminopyridyl Ligands: Structural, Photophysical, and co2 Electrocatalytic Reduction Studies - Levín-Vásquez, P; Levín-Vásquez, P (Elsevier B.V., 2025)
Five rhenium complexes [Re(CO)3(N,N)Cl] (C1–5), in which N,N represents iminopyridyl ligands, were successfully synthesized. The structural characterization of these compounds includes NMR, FT-IR, and HRMS analyses. Additionally, the molecular structures of C2 and C3 were determined through X-ray diffraction analysis. Electrochemical characterization indicates a metal-centered HOMO and a ligand-centered LUMO, with the latter strongly influenced by the nature of the substituent. The photophysical properties of all complexes were examined using UV–Vis spectroscopy and spectrofluorometric measurements in dichloromethane solution at room temperature, as well as in the solid state. All complexes exhibit a spin-allowed MLCT absorption transition in the 405–471 nm range. In degassed dichloromethane solution at room temperature, complexes C1–3 and C5 display an unstructured (Kinzel et al., 20213)MLCT emission in the red region of the visible spectrum. In contrast, complex C4, which features the lower-energy absorption, is nearly non-luminescent. Conversely, all complexes show emission in the solid state, with bands presenting a distinctive hypsochromic shift characteristic of MLCT states. Finally, all compounds were evaluated for their ability to promote the electrocatalytic reduction of CO2, showing turnover frequencies (TOFs) ranging from 8.1 to 304.4 s−1. © 2024